Rectification of nanopores in aprotic solvents – transport properties of nanopores with surface dipoles. Issue 45 (2nd November 2015) - Plett, Timothy; Shi, Wenqing; Zeng, Yuhan; Mann, William; Vlassiouk, Ivan; Baker, Lane A.; Siwy, Zuzanna S.
Abstract : Surface dipoles rendered by adsorbed solvent molecules influence ionic transport at nanoscale. Abstract : Nanopores have become a model system to understand transport properties at the nanoscale. We report experiments and modeling of ionic current in aprotic solvents with different dipole moments through conically shaped nanopores in a polycarbonate film and through glass nanopipettes. We focus on solutions of the salt LiClO4, which is of great importance in modeling lithium based batteries. Results presented suggest ion current rectification observed results from two effects: (i) adsorption of Li + ions to the pore walls, and (ii) a finite dipole moment rendered by adsorbed solvent molecules. Properties of surfaces in various solvents were probed by means of scanning ion conductance microscopy, which confirmed existence of an effectively positive surface potential in aprotic solvents with high dipole moments.